Key metrics to measure the performance and impact of reusable packaging in circular supply chains - Betts, Kellen; Gutierrez-Franco, Edgar; Ponce-Cueto, Eva (Frontiers in Sustainability, 2022)
Circular supply chains comprise the industrial production and supply chain systems used by companies to eliminate waste and recover value in products and materials. There are a variety of circular strategies including recycling in waste management, returns and repair in consumer-facing industries, and reusable packaging in supply chains. Successful implementation and management of these circular strategies requires the ability to measure and report on progress across different functions and processes. In this paper, we propose a new set of metrics to measure the performance of reusing items in a circular supply chain. We review the literature on metrics in circular supply chain management and reusable packaging in supply chains. We then classify the proposed metrics based on whether they measure the circularity of a circular supply chain initiative or impact of implementing the initiative. They also are segmented based on the level of detail they incorporate from the product level to the system level. We then demonstrate the use of the proposed metrics through a case study with an omnichannel retail company. We find that product-level metrics facilitate the comparison of different types of reusable and single-use packages with the potential to reduce lifecycle greenhouse gas emissions. We also find that measuring system-level Total Logistics Costs helps identify potential challenges with the feasibility of a reusable packaging system including the implications of not recovering packages and amortizing initial costs across multiple use cycles. Our aim in this paper is to address the gap in circularity and impact metrics focused on reuse strategies in supply chains. This new set of metrics provides companies with a tool to measure and report on progress toward a circular economy. It also suggests future avenues for research to assess the economic, environmental, and social dimensions of sustainability.